Reclaiming the vision: challenges of Indian constitutional law and governance - Rao, P. P. (Gurgaon, 2013)
This book contains a selection of articles and speeches by a distinguished senior advocate, as well as greatly respected teacher-scholar. In it he shares his thoughts, deeply cherished beliefs, and concerns about critical facets of law, governance, and constitutional leadership in India. He reminds us that those who framed the Constitution had a vision of inclusive justice and progress for all. He suggests that the Constitution has been inadequately administered in India and throws light on a wide range of issues. He forcefully argues for radical and comprehensive reforms in governmental functioning. He throws light on key unresolved contemporary challenges such as the reality of gender discrimination, corruption in the judiciary, and the system of judicial appointments. He explains how famous, but little understood cases, like Kesavananda Bharati, TMA Pai, Indra Sawhney, Sajjan Singh, Sankari Prasad, Indira Nehru Gandhi, IR Coelho have made a major impact on governance. Keenly aware of the important role of the legal profession in tackling the problems facing the country, he calls uncompromisingly for a return to high professional standards and values. A unique collection, this book will be of interest not only to members of the legal profession, the judiciary, political scientists, social activists, students and journalists, but all those who wish to understand what our Constitution stands for and the challenges that lie ahead.
Keywords: Constitution-India